Studying on Infrared Stealth Property of Polyurethane Coatings - Liang, Chengcong; Li, Ping (Asian Journal of Chemistry, 2013)
In general, polyurethane coatings, acrylic polyurethane coatings and organosilicon coatings are all high infrared emittance. But they have excellent chemical resistance, weather-proof and better mechanical property, such as good metal adhesive. In this paper we studied infrared property, physical and chemical properties by contrast with polyurethane coatings, acrylic polyurethane coatings and organosilicon coatings. From the experiment we selected polyurethane coatings as infrared stealth adhesive. By the method of adding fillers to polyurethane coatings and changing coatings techniques, low infrared emittance can be gained. Using polyurethane coatings as adhesive and sheet aluminium, SiO2 powder and so on as fillers, we got aqua coat and its infrared emissivity is 0.33. At the same time we found conductance and reluctivity are high effect on infrared emissivity of coating.